DESIGNING SCIENCE LEARNING MATERIALS BASED ON BAU NYALE LOCAL WISDOM ON THE TOPIC OF EARTH’S ROTATION AND REVOLUTION FOR PRIMARY SCHOOL - Suranti, Ni Made Yeni; Ibrahim, Ibrahim; Gusfian, Mauliana (BIOCHEPHY: Journal of Science Education, 2025)
This study aims to develop science learning materials based on local wisdom by linking natural phenomena, specifically the topics of Earth's rotation and revolution, with the Bau Nyale tradition. This tradition, rooted in the Sasak community of Lombok, is closely related to lunar phases, seasonal changes, and marine ecosystems. The development of the learning materials is intended to foster students’ critical thinking skills while preserving local culture. The method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate), although this study is limited to the define and design stages. The define stage involved needs analysis through literature review and questionnaire distribution, which revealed a low level of student understanding of scientific content and limited integration of local cultural values in learning. The design stage resulted in an interactive prototype of instructional materials in the form of a PowerPoint presentation that integrates scientific content with local cultural context. The findings indicate that this approach has the potential to enhance students’ understanding of Earth’s rotation and revolution in a contextual manner, while also promoting critical thinking skills and appreciation for cultural heritage. The developed learning materials are expected to serve as relevant and contextual resources for science learning in primary education.